DERIVED EQUATIONS FOR DAMAGE ACCUMULATION IN GEARED WHEELS BASED ON MODIFIED LAWS OF CRACK PROPAGATION - Józef DREWNIAK; Jacek RYSIŃSKI (Scientific Journal of Silesian University of Technology. Series Transport, 2016)
Versatile hypotheses of fatigue damage accumulation are utilized in order to determine the fatigue life of particular mechanical elements. Such an approach to an analysis of fatigue processes is recognized as being phenomenological. In the present paper, modifications to the Paris and Foreman laws of fracture mechanics have been proposed. The goal of these modifications is an explicit formulation of crack propagation velocity as a function of crack length. Additionally, the process of crack growth was simulated according to the Palmgren-Miner and Pugno-Ciavarella-Cornetti-Carpinteri fatigue hypotheses. The results of simulation were verified based upon test stand experiments.